Reassessment of treadmill stress testing for risk stratification in patients with acute myocardial infarction treated by thrombolysis. Issue 5 (November 1993) - Stevenson, R; Umachandran, V; Ranjadayalan, K; Wilkinson, P; Marchant, B; Timmis, A D
Abstract : OBJECTIVES--To evaluate the role of a treadmill stress test for identifying patients at risk of recurrent ischaemic events after acute myocardial infarction treated by thrombolysis. BACKGROUND--The natural history of myocardial infarction has changed with the introduction of thrombolytic treatment; there is a lower mortality but a higher incidence of recurrent thrombotic events (reinfarction, unstable angina). The treadmill stress continues to be recommended for risk stratification after acute myocardial infarction even though its value has never been formally reassessed in the thrombolytic era. METHODS--Prospective observational study in which 256 consecutive patients who presented with acute myocardial infarction treated by thrombolysis underwent an early treadmill stress test and were followed up for 10 (range 6-12) months. RESULTS--Recurrent ischaemic events occurred in 41 patients (unstable angina 15, reinfarction 21, death five) and a further 21 required revascularisation. Both ST depression at a low workload and low exercise tolerance (< 7 metabolic equivalents of the task (METS) were predictive of recurrent events, with respective hazard ratios of 1.93 (95% confidence interval (95% CI) 1.17-3.20; p < 0.01)) and 1.67 (95% CI 1.0-2.78; p < 0.05). These variables identified 50% and 70% of patients who subsequently sustained a recurrent ischaemic event, but the corresponding values for positive predictive accuracy were only 26% and 21%. Thus they are of limited value as a screening measure for identifying patients likely to benefit from invasive investigation and revascularisation. None of the other variables (ST elevation, haemodynamic responses, ventricular extrasystoles, angina) was significantly associated with recurrent ischaemic events. CONCLUSIONS--The treadmill stress test is of limited value for identifying patients at risk of recurrent ischaemic events after acute myocardial infarction treated by thrombolysis.